Sartre e a liberdade na literatura, filosofia e dramaturgia - Silva Neto, Fernando Alves (2017)
This dissertation aimed to research the concept of freedom in Sartre's work, approaching it in different scenarios: Literature, Philosophy and Dramaturgy. For this, the initial analysis of the research focused on Sartre's definition of "literature", aiming to clarify the formal structures of literary art, by means of What is Literature? (1947), work where the philosopher deals directly with this specific sort of art. After that, it sought to understand "freedom" along the Part One of Being and nothingness (1943), intending to clarify the ontological foundation of Man: being that is what it isn't and that's not what it is. To investigate that paradox about Man is fundamental to understand Sartre's goal, for it would lead him to present a mystified/demystified freedom in Theater. The focus, then, remained on presenting, along the text, the development of that theme, delimiting it into three specific moments: the first of them, to understand what it is "literary art" for Sartre; the second one, the For-Itself as "being-free and indefinite"; and the third, Theater as a "theater of freedom"